Perception of University Students on the Achievement of Disaster Nursing Course Competencies with Online Learning Methods - Dhiya Roihana; Etika Emaliyawati; Sandra Pebrianti (Sean Institute, 2023)
The COVID-19 pandemic has had an impact on the teaching and learning process, namely online learning methods which have made several changes, especially in subjects that require practical competence. According to the International Council of Nurses, nursing students must have appropriate knowledge of competence in dealing with disaster problems. This study aims to describe student perceptions of the competency achievements of the Disaster Nursing Course using online learning methods at the Faculty of Nursing, Universitas Padjadjaran. The research design uses quantitative descriptive with a cross sectional approach using the Nurse Perception of Disaster Core Competencies Scale instrument. The population in this study numbered 155 students from class 2018 using the purposive consecutive technique. The data were analyzed using univariate analysis which measured student perceptions with results supporting or not supporting. The results of the analysis showed that more than half of the students had unfavorable perceptions, namely 85 students (54.8%) and supportive perceptions, namely 70 students (45.2%). The results of the sub variable critical thinking (62.6%) did not support, assessment (53.5%) did not support, communication (56.1%) did not support, and technical skills (51.6%) did not support. Students' perceptions of competency achievement in disaster nursing courses using online learning methods are not supportive, both in the total score of perceptions about the achievements of all core competencies and in sub-variables. Suggestions for educational institutions to hold seminars/training, practicum, and simulations related to the competence of disaster nursing courses in online learning methods.